Analisis Pengaruh Profitability dan Leverage Terhadap Nilai Perusahaan Pada Perusahaan Berbasis Konsumen - Leonardo, Lauren; Tjahjono, Rudi Setiadi (Media Bisnis, 2024)
The purpose of this study is to obtain empirical evidence where the independent variables, which are profitability, liquidity, firm size, dividend policy, institutional ownership, and investment decision have an influence on firm value as dependent variable. In this study, the population used was consumer non-cyclical and consumer cyclical companies that listed on Indonesian Stock Exchange from 2020 to 2022 using the purposive sampling method. The data obtained was 111 sample data from consumer non-cyclical and consumer cyclical company for the period 2020 to 2022. After testing the residual normaliity for outliers, the research has resulted on 109 data sample. The test used in this study is multiple regression which helps to determine the influence among the dependent variable and the independent variable. The results of this study indicate that independent variables such as profitablity and leverage have an effect on firm value where liquidity, firm size, dividend policy, institutional ownership, and investment decision have no effect on firm value.